Beyond the Ledger: Reconciling Financial Accountability and School Well-being in Public Education - Suwarniti, Urip; Wuryandini, Endang; Muhtarom, Muhtarom (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
The implementation of school well-being requires adequate financial support, but is often hampered by the complexity of budget management, limited specific funding allocations, and difficulties in aligning regulatory compliance with student welfare priorities. This study aims to analyze financial management to support school well-being, focusing on planning, organization, implementation, and supervision, as well as its relationship to the School Operational Assistance (BOS) mechanism, public school governance, and financial accountability. The research approach used a case study design, with data collection through in-depth interviews, participant observation, and documentation studies. Informants were selected using purposive sampling, while data analysis was conducted interactively through reduction, presentation, and drawing conclusions. The results show that participatory, data-driven financial planning improves allocation accuracy, organization is supported by task allocation and the BOS Management Team, implementation promotes administrative transparency, and supervision strengthens financial accountability through monitoring, internal audits, and school committee involvement. The implications of this research are the development of an operational model for financial management that integrates the BOS mechanism, public school governance principles, and financial accountability practices as a reference for policymakers and school administrators.